Relationship between Knowledge of Maternal Nutrition and Diet with Nutritional Status of Toddlers in the Work Area of the Sidomulyo Health Center, Samarinda City - Syarifah Nur Intani; Satriani; Jamil Anshory (PT FORMOSA CENDEKIA GLOBAL, 2022)
Nutritional problems in toddlers affect intake and infectious diseases. Food intake that is not optimal causes problems in nutrition. This study aims to determine the relationship between mother's nutritional knowledge and toddler's diet with toddler's nutritional status. Using a cross-sectional design study. This sample was carried out by probability sampling with purposive sampling method. Statistical analysis using chi-square test. The research location is in the work area of ​​the Sidomulyo Public Health Center, Samarinda City. Data on maternal nutritional knowledge and toddler eating patterns were obtained through interviews using a questionnaire and 24-hour food recall. Meanwhile, the nutritional status of toddlers is measured by measuring their weight and height. There is a relationship between mother's knowledge and eating patterns with the nutritional status of toddlers. From the results of the study there is a relationship between mother's knowledge and eating patterns with the nutritional status of toddlers.